STRATEGI PENGEMBANGAN PARIWISATA ALTERNATIF DI DESA PELAGA KECAMATAN PETANG KABUPATEN BADUNG - I Ketut Antara (Jurnal Ilmiah Hospitality Management, 2011)
Based on the Regulation of Regent of Badung Number: 47 Year 2010 concerning Determination of Destinations in Badung Tourism Village, Badung Regency has eleven regional tourist village. One of them developed a decent tourist village is Pelaga Village located at Petang District. It is substantially developed as a community based Tourism destination. Issues raised in this research are: (1) The possibilities for what that support Pelaga Village to be developed as a tourist attraction; (2) How Pelaga village community support of village development plans such as a tourist attraction; and (3) How Pelaga Village Development Strategy as a tourist attraction.The purpose of this research are: (1) To determine the potential Pelaga Village as a tourist attraction; (2) To know the local community support at Pelaga Village of village development plans as a Tourist Attraction; (3) To know the Village Development Strategy as an alternative tourism.The data used in this research is qualitative and quantitative data which a purposive sample taken. The data has been collected and analyzed by descriptive qualitative and SWOT analysis. The results of this study indicate, that Pelaga Village tourist attractive destination has a decent variety of tourism potential to be developed and has met four (4) an important component in the tourism industry which is known as the four A's: Attraction (tourist attractions), Accessibility (access to reach the tourist areas) , Amenity (facilities and tourism services), and ancillary (institutional and human resources supporting tourism). In addition, the local communities are involved directly in providing of tourism support facilities and in developing Pelaga Village. In the future Pelaga Village can be developed by implementing some strategies such as strategic SWOT ; SO, ST, WO, and WT strategies. The results of this study are expected can give some positive contributions in planning, developing strategies for Pelaga Village in the future time, one day it will give a good impact on the development and economic growth and social and cultural life of local communities.